Pemanfaatan Media Video Tutorial Youtube untuk Meningkatkan Permainan Bulutangkis pada Mata Pelajaran Penjasorkes Siswa SMP Kelas VIII-3 - Juhaeni Juhaeni (Universtas Negeri Makassar, 2022)
The purpose of this study was to improve the learning outcomes of Physical Education, Sports and Health of students through the Utilization of YouTube Video Tutorial Media to Improve Badminton Games in Physical Education Subjects for Grade VIII-3 Students of SMP Negeri 3 Barru in the 2017/2018 Academic Year. The research method used is Classroom Action Research with implementation stages which include: (1) planning, (2) implementation, (3) observation and evaluation, (4) reflection. This research was conducted at SMP Negeri 3 Barru, Barru District, Barru Regency, with a total of 32 class VIII.3 students as research subjects. The conclusion of activity, creativity, students' responses to game material, the activity of observing YouTube video tutorials about playing badminton with all its techniques and exploring them greatly increased in cycle II. In addition, it appears that cooperation, collaboration, interaction between students is increasing in learning.